Application of Artificial Intelligence in drug discovery, designing, clinical trials and repurposing - Agrawal, Rashmi; Kulkarni, Meghashyama (Indian Journal of Pharmacy & Drug Studies, 2025)
Drug development, right from discovery, designing, and repurposing, along with various phases to clinical trials, is a complex and time-consuming process that traditionally relies on the experience of labor forces, along with incessant trial-and-error experimentation. The emergence of various artificial intelligence (AI) tools and techniques is redefining the pharmaceutical industry. The integration of AI-driven methodologies into all stages of the drug development pipeline has enhanced the efficiency and effectiveness of the process. With this review, we aim to provide insights into the application of AI at various stages mentioned, with an emphasis on the latest advancements. The role of AI in speeding up the process of drug development while giving distinct and accurate outcomes is highlighted as well. Finally, we addressed the current challenges in employing AI along with future perspectives in order to enhance AI-augmented drug development, ultimately offering significant benefits to patients and society.